Assessing the Diagnostic Accuracy of Physicians for Home Death Certification in Shanghai: Application of SmartVA - Chen, Lei; Xia, Tian; Rampatige, Rasika; Li, Hang; Adair, Tim; Joshi, Rohina; Gu, Zhen; Yu, Huiting; Fang, Bo; McLaughlin, Deirdre; Lopez, Alan D.; Wang, Chunfang; et al. (Frontiers in Public Health, 2022)
Approximately 30% of deaths in Shanghai either occur at home or are not medically attended. The recorded cause of death (COD) in these cases may not be reliable. We applied the Smart Verbal Autopsy (VA) tool to assign the COD for a representative sample of home deaths certified by 16 community health centers (CHCs) from three districts in Shanghai, from December 2017 to June 2018. The results were compared with diagnoses from routine practice to ascertain the added value of using SmartVA. Overall, cause-specific mortality fraction (CSMF) accuracy improved from 0.93 (93%) to 0.96 after the application of SmartVA. A comparison with a “gold standard (GS)” diagnoses obtained from a parallel medical record review investigation found that 86.3% of the initial diagnoses made by the CHCs were assigned the correct COD, increasing to 90.5% after the application of SmartVA. We conclude that routine application of SmartVA is not indicated for general use in CHCs, although the tool did improve diagnostic accuracy for residual causes, such as other or ill-defined cancers and non-communicable diseases.